Proposed Marketing and Its Implementation for RSH Housing in Kecamatan Sematang Borang (Case Study: PT Hanafia Property) - Apriadi, Andi Hanafiputra; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract-- RSH (Simple Healthy Home) is a home built using simple building materials and construction but still meet the minimum requirements of health, safety, and comfort. The RSH housing business in South Sumatra is a huge opportunity, so that PT. Hanafia Property (PT. HP), a property company, tries to take this opportunity by building Borang Housing in Kecamatan Sematang Borang, Palembang. The current problem is PT. HP needs to develop marketing strategy for Borang Housing. The conceptual framework is expected to provide a broader view to analyze and to provide solutions for the company's marketing strategy. Situation analysis uses the 5Cs that shows the market in Sematang Borang is attractive. Through STP analysis, the company targets lower middle class through the affordable RSH supported by complete facilities and infrastructure. The strategy formulation starts with choosing business strategy, and PT. HP chooses as follower position (me-too strategy) to avoid direct competition with other companies that has entered the RSH market. Next from Marketing Mix strategy, HP offers units that meet not only physical needs but also (augmented product) emotional benefit. Borang Housing also provides complete residential facilities to be enjoyed by the buyers in the housing complex. The housing offers low prices with ease of payment. HP uses a familiar name and recognizable by consumers for RSH housing, Borang Mandiri Residence. The implementation plan contains the explanation of marketing mix programs to be run, functions in the company which are responsible, and budget needed. The period is three phases totaled in 3 years, and with total budget of around Rp. 770 million. The evaluation of the marketing strategies is done through benchmarking,, number of inquiris, and ratio of inquiry with sales.Â Key Words: Hanafia Property, Marketing Strategy, Marketing MixÂ